Pengenalan cita-cita melalui fun learning untuk meningkatkan minat belajar siswa taman kanak-kanak - Natalia, Vicencia Giovenna; Gunawan, Marvel; Pertiwi, Dewi (Nur Science Institute, 2024)
This community service aims to enhance students' interest in learning at TK Karitas V, Surabaya, by introducing future goals through fun learning. Early childhood education, which falls within the golden age phase, requires teaching methods that can enhance children's focus, considering that children often face emotional instability during this period. In an effort to achieve this goal, the introduction of future goals is implemented through an engaging and interactive learning model, utilizing playful activities and musical movements to create an enjoyable and meaningful learning experience, thus enhancing the students' learning interest. The method used in this community service is service learning, involving direct interaction with children to create strong emotional bonds and interactions. The results of this community service show changes before and after participation among TK Karitas V students. Students demonstrate increased enthusiasm and eagerness to learn in pursuit of their dreams. Students also show improvement in their ability to understand and interpret aspirations related to their future.